Chlorine dioxide inactivation of Pseudomonas aeruginosa and Staphylococcus aureus in water: The kinetics and mechanism. (December 2018) - Ofori, Isaac; Maddila, Suresh; Lin, Johnson; Jonnalagadda, Sreekantha B.
Graphical abstract: Abstract: This study evaluated the inactivation kinetics and the bactericidal mechanism of chlorine dioxide towards Pseudomonas aeruginosa (ATCC 27853) and Staphylococcus aureus (ATCC 29213) on a laboratory scale with the view of determining the optimal operational conditions of its application as an alternative disinfectant in water treatment. Bacteria inactivation was conducted in batch reactors at varied disinfectant concentrations, pH, temperature and initial bacteria densities in buffered disinfectant demand free water. The bactericidal mechanism in terms of the effect on the permeability of the outer and cytoplasmic cell membranes and the morphology of the cells were explored. At the highest studied concentration (5.0 mg/L), at least 5-log reductions in bacterial population were observed for each strain of bacteria. Chlorine dioxide inactivation showed a stronger sensitivity to changes in water pH conditions with the inactivation rate at 8.5 being at least 4-fold of what pertained at 6.5 but efficiency was less impacted by changes in the initial bacteria density. A rise in temperature from 4 °C to 15 °C resulted in approximately 56% increase in the inactivation rate of S. aureus . Chlorine dioxide was found to increase the permeability of outer and cytoplasmic cell membranes and consequently resulting in the release of vital nuclear materials which strongly correlated with loss of cell activity or death. However, from TEM micrographs significant morphological damages or cells lysis was not observed. These results provide vital data on operational strategies to enhance efficient disinfection of water with chlorine dioxide whilst monitoring regulatory requirements on disinfection by-products.